Réponses

  • Utilisateur Brainly
2014-03-16T20:36:49+01:00
Résoudre dans R les équations : 

(E1) : f(x) = 2(x-1)(x-5) = 0
           x-1=0 ou x-5=0
           x=1 ou x=5

(E2) : g(x) = -2(x-3)(x-5) = 0
                 x-3=0 ou x-5=0
                 x=3 ou x=5

Montrer que pour tout x de R :

  2(x-3)² -8 = f(x)         et                 -2(x-4)² +2 = g(x)

f(x)=2(x-1)(x-5)
=2(x²-6x+5)
=2(x²-6x)+10
=2(x-3)²-18+10
=2(x-3)²-8

g(x)=2(3-x)(x-5)
      =-2(x²-8x+15)
     =-2(x²-8x)-30
     =-2(x-4)²+32-30
     =-2(x-4)²+2